2021
DOI: 10.1007/s40194-021-01096-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of joints from laser powder fusion processed and conventional material grades of 18MAR300 nickel maraging steel

Abstract: Even though the buildup rate of laser powder bed fusion processes (LPBF) has steadily increased in recent years by using more and more powerful laser systems, the production of large-volume parts is still extremely cost-intensive. Joining of an additively manufactured complex part to a high-volume part made of conventional material is a promising technology to enhance economics. Today, constructors have to select the most economical joining process with respect to the individual field of application. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, 18 Ni −250 (X2NiCoMo 18-8-5) and 18 Ni 200 are referred to as Fe Ni alloys [34]. A metal-based printing techniques in additive manufacturing can be classified as Selective Laser Melting, Electron Power Bed Fusion, Direct Energy Deposition and Laser Power Bed Fusion [35][36][37][38][39][40][41][42].…”
Section: Features Of Maraging Steelsmentioning
confidence: 99%
“…For example, 18 Ni −250 (X2NiCoMo 18-8-5) and 18 Ni 200 are referred to as Fe Ni alloys [34]. A metal-based printing techniques in additive manufacturing can be classified as Selective Laser Melting, Electron Power Bed Fusion, Direct Energy Deposition and Laser Power Bed Fusion [35][36][37][38][39][40][41][42].…”
Section: Features Of Maraging Steelsmentioning
confidence: 99%
“…In another study, we were able to prove that LPBF/LPBF joints and hybrid joints of LPBF and conventional material grades for AISI 18MAR300 provide a significantly higher tensile strength of 972 MPa (SD: 20) or respectively 904 MPa (SD: 38) when using AuNi18 brazing filler metal which does not require a nickel‐plated surface. [ 17 ] Furthermore, it was shown that if the LPBF part is directly build‐up onto a conventional material grade and then solution annealed and precipitation hardened without brazing, the tensile strength was 1998 MPa (SD: 62). However, it could also be shown that the imperfections within the LPBF microstructure (interlayer defects, unmolten particles, keyhole voids, and oxide inclusions) affect the tensile strength and the increased load fatigue strength as well for the solid material which is also reported by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] However, the costs of the powder as well as the slow layer by layer process limit an economic production of high-volume components, even with respect to the using of hull-and-core strategy. [17][18][19] Since the required component functionality is often only required locally, it is obvious to join an LPBF part with high functionality to conventionally produced material (e.g., for clamping of the component). [20][21][22][23] As mentioned earlier, the complex oxide layer of maraging steels is difficult to wet by brazing alloys due to the DOI: 10.1002/srin.202300108 Laser powder bed fusion (LPBF) processes offer the best possible design options for the production of highly complex components with unique functionalities.…”
Section: Introductionmentioning
confidence: 99%